Pengembangan Media Pembelajaran Simulasi Kontrol Motor Listrik Hidup Bergantian Menggunakan Programmable Logic Controller (PLC) - made satria pandu sancaya; Agus Adiarta; I Gede Ratnaya (Universitas Pendidikan Ganesha, 2021)
This study aims to create learning media for alternating living electric motor control simulations using a Programmable Logic Controller (PLC) to determine the feasibility, as well as knowing the responses of students to Learning Media for Alternating Living Electric Motor Control Simulation using Programmable Logic Controller (PLC) in the subject of Electrical Motor Installation. at SMK Negeri 3 Singaraja. This study uses a Research and Development (R&D) research and development method. Data collection in this study was carried out by distributing questionnaires which were assessed by content/material experts, media experts, and class XII students majoring in Electrical Power Installation Engineering at SMK Negeri 3 Singaraja. The results obtained: the results of the validation test from the media expert get a percentage of 90.00% including very feasible qualifications, and the results of the content / material expert validation test get a percentage of 94.00% including very feasible qualifications. The results of the small group trial with 5 respondents, 1 respondent was in the neutral category with a percentage of 20%, and 4 others were categorized as strongly agree with a percentage of 8. In the results of the large group test with 20 respondents, 19 respondents were categorized as strongly agree with a percentage of 95%, and 1 respondent was in the neutral category with a percentage of 5%. Based on the research results, the Learning Media for Alternating Living Electric Motor Control Simulation using a Programmable Logic Controller (PLC) is feasible for use in the electric motor installation practicum activity.